The Influence of Local Culture on Islamic Education in Indonesia - Azmillulloh Askarul Jabar; Sania Aqil Salsabila (Socrates: Journal of Education, Philosophy and Psychology, 2024)
The influence of local culture on Islamic education in Indonesia is reflected in the integration of cultural values into the curriculum, teaching methods, and interactions within educational environments. Indonesia’s cultural diversity creates opportunities for harmonization between local traditions and Islamic teachings, ultimately enriching students’ learning experiences. Values such as mutual cooperation, local wisdom, and social norms contribute to shaping students’ character in understanding and practicing Islamic teachings. This integration not only strengthens Islamic identity but also enhances the education system with a more contextual and inclusive approach. Keywords: Local Culture, Islamic Education, Cultural Values, Cultural Integration, Indonesia.